FAKTOR INTERNAL DAN FAKTOR EKSTERNAL PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PROVINSI JAWA TENGAH TAHUN 1994 - 2010 - Putri, Hera Pradipta; Poerwono, Dwisetia (Diponegoro Journal of Economics, 2013)
This studi aimed to determine internal and external factors that influence Gross Domestic Product (GDP) of Centra Java Province from 1994 to 2010. The purpose of thus study is based on the problem of low Gross Domestic Product (GDP) of Central Java Province. Gross Domestic Product (GDP) an area influenced by internal and external factors, as well as to GDP of Central Java Province which is also influenced by internal and external factors. Internal factors are factors that originate from within the region itself, whereas external factors are factors that originate from outside the region. In this study are included in the internal factors are local government spending, private investments, and prices of domestic goods in Central Java Province, while belonging to the external factors are GDP of West Java Province and East Java Province.The data used in this study is secondary data. Data taken at government agencies. Analysis method that is used is OLS method were analyzed using analysis tools eviews 6. The dependent variable in this study is GDP of Central Java Province, and the independent variables in this study are GDP of West Java Province, GDP of East Java Province, local government spending of Central Java Province, private investments in Central Java Province, and prices of domestic goods in Central Java Province. The Results of this study show that internal and external factors alike – each has and influence on GDP of Central Java Province. External factor have more influence on GDP of Central Java Province than internal factor. Independent variable that have a significant impact on GDP of Central Java Province are GDP of West Java Province and GDP of East Java Province.